Manajemen Pendidikan Dasar Islam: Konsep Dasar dan Landasan Pengelolaan - Winarti, Endah; Abidin, Zainal (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2022)
The goals of Islamic basic education must not misdirected, so management skills are needed that are based on an understanding of Islamic education management science. The aim of the research is to examine the basic concepts of Islamic basic education management and the foundations that become the fulcrum in management. It is hoped that the results of the study can serve as a guide for administrators of Islamic basic education. The role of Islamic basic education is very strategic because it is the level that forms the basis for further education. In order to build a strong Islamic basic education management concept, an understanding of a number of foundations is needed which is the foundation in the practice of managing Islamic basic education institutions. Through literature studies, the results of the study provide guidance for managers of Islamic basic education institutions in terms of basic Islamic education management, including: philosophical basis, religious basis, sociological-anthropological basis, psychological basis and juridical basis.